Geomorfological assessment on the environmental analysis of the Serra das Confusões National Park- Piauí State - Brazil - Rocha, André Magalhães; Marçal, Mônica dos Santos; Guerra, Antonio José Teixeira (Sociedade & Natureza, 2005)
The Serra das Confusões National Park is the largest park in northeastern Brazil, witha total area of 502902ha, including 9 municipalities, all in Piauí State, with the headquarterslocated in Caracol City.The Park is situated on the top of a plateau, latitude 8°30'S; 9°30'S, longitude 43°W;44°W, drained by channels which flow northwards to Parnaíba river, the main river of PiauíState.Serra das Confusões National Park area is in on morphoestructural andmorphoclimatical units inside the Piauí-Maranhão sedimentary basin plateau of theinterplateau depression with a semiarid domain, covered by caatinga vegetation(RADAMBRASIL, 1973). The transition zone between Caatinga and Cerrado on the plateau,depressions and complex areas has a vegetation named Carrasco.This paper aims to show a preliminary version regarding geology, geomorphology,pedology and hydrological dynamics on the environmental characterization of the Park andtherefore to identify risk areas, to create a use planning and management for the area toimprove a better use for these potentials.The Parks geomorphological analysis can be justified by the high importance tounderstand the natural and social reality of the National Park, showing restrictions on use,always aiming the sustainability of the ecosystem delicate equilibrium, the physicalenvironment, together with the visitor's safety.